Tribology of zrn, crn and tialn thin films deposited by reactive magnetron sputtering (2013)
Friction and wear coefficient represent two important variables for hard coating selection in critical engineering applications such as cutting and material forming. To explain fully these variables, is necessary to understand different types of wear mechanisms that occur in coated surfaces. Zirconium nitride (ZrN), chromium nitride (CrN) and titanium aluminum nitride (TiAlN) coatings produced by reactive magnetron sputtering technique were evaluated. The tribological properties- coefficient of friction (COF) and wear coefficient were investigated using a ball on disc tribometer and profilometry. Bias polarization voltage showed an increase in plastic deformation and third body generation failures in the ZrN surface. Nitrogen flux increasing in CrN deposition, improves tribological behavior due to cubic phase segregation, enhancing superficial properties. Increasing substrate temperature during deposition of TiAlN improves superficial properties (roughness and porous density decrease), increases abrasion wear resistance and load capability of the coating.